PENGARUH COUNTRY OF ORIGIN PERCEPTION, PERCEIVED QUALITY DAN PROMOTIONAL MIX TERHADAP PURCHASE INTENTION DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (STUDI PADA SMARTPHONE BUATAN INDONESIA) - Ni Made Rastini; I Nyoman Nurcaya (Universitas Trunojoyo Madura, 2018)
ABSTRACTThis study aims to analyze the influence of Country of Origin Perception, Perceived Quality and Promotion on Brand Image and Purchase Intention. Then to analyze whether Brand Image always affect consumers to make purchases of products especially smartphones made in Indonesia. To achieve that goal used as many as 125 respondents taken by purposive sampling with questionnaires as a method of data collection. The data is processed by means of analysis of Structural Equation Modeling. The results show that Country of Origin Perception, Perceived Quality and Promotion affect Purchase Intention either without or through Brand Image. Thus, it is suggested that Indonesian smartphone business players are expected to increase their promotion intensity and product performance in order to be able to build a consumer brand image that will ultimately affect the buying interest of Indonesian smartphone consumers.